Application of the cause and effect diagram in the diagnosis of high energy consumption: A case study in the management and production sectors of the Tomé-Açu Mixed Agricultural Cooperative - CAMTA (Research, Society and Development, 2020)
This article is sought by means of field research, to analyze how the electrical energy is consumed within the CAMTA (Cooperativa Agrícola Mista de Tomé-Açu), which has as its main activity or process and commercialization of fruit pulps, in a way Generally, the purpose of identifying the main problems that generate a high consumption of electricity in the company. The surveyed areas involve administrative, process, laboratory and armature sectors where the cold stores are located. The methods used for an interview and application of a questionnaire. Or software used for tabulation of two data was Excel and as ferramenta for exposition of two results used or Diagram of Cause and Effect without X-Mind software. From the investigation, I know that the stock of the pulps is more demanding of energy, a greater part of the consumption of the armature of the cold rooms, as well as not having automatic temperature regulation. Another factor is the obsolescence of machines, which contributed to high consumption, or which reduced operational capacity, in addition, the constant repairs, with adjustments of low added value, interference potential of two equipment. Such adjustments are corrective, and sporadically preventive. It is verified that the demand is higher than the supply, this form, or operation is given in 24 hours without the harvest period (açaí), due to the inefficiency of the machinery, it hardly meets the needs of two consumers, and, therefore, increases or cost with electricity, mainly not peak hours.